2016
DOI: 10.1108/dpm-01-2016-0014
|View full text |Cite
|
Sign up to set email alerts
|

The Deepwater Horizon oil spill and factors associated with depressive symptoms among residents of the Mississippi Gulf Coast

Abstract: Purpose – The purpose of the paper is to extend prior research on the psychological effects of the Deepwater Horizon oil spill disaster by developing and testing a conceptual model in which exposure to the oil spill through clean-up activity, physical symptoms, worry about the impact of the oil spill on health, and the disruption of the gulf/ocean-related lifestyle were hypothesized as predictors of depressive symptoms. Design/methodology/approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The development of alterations in hematological profile and liver function was part of the risk expected by people who participated in the clean-up exercise (D'Andrea & Reddy, 2013). Also, Lee et al, (2016) conducted a study on the impact of the Deepwater Horizon oil spill on depressive health symptoms among residents of Mississippi Coast and related lifestyle. And their findings showed the exposure of the clean-up workers and residents resulted in great depressive symptoms which also disrupted the gulf/ocean-related lifestyle.…”
Section: Response and Clean-up Operations In Event Of Oil Spillagementioning
confidence: 99%
See 1 more Smart Citation
“…The development of alterations in hematological profile and liver function was part of the risk expected by people who participated in the clean-up exercise (D'Andrea & Reddy, 2013). Also, Lee et al, (2016) conducted a study on the impact of the Deepwater Horizon oil spill on depressive health symptoms among residents of Mississippi Coast and related lifestyle. And their findings showed the exposure of the clean-up workers and residents resulted in great depressive symptoms which also disrupted the gulf/ocean-related lifestyle.…”
Section: Response and Clean-up Operations In Event Of Oil Spillagementioning
confidence: 99%
“…The health impact of oil spill on the clean-up workers and other humans closer to the spill location were investigated in various researches and findings showed a lot of negative health impacts (Lee et al, 2016;Stanbury et al, 2010;Sholeye et al, 2012;D'Andrea & Reddy, 2013;Shultz et al, 2014;Gill et al, 2012;Jung et al, 2017;Ha et al, 2012;Choi et al, 2016). Peres et al, (2016) found short-and long-term physical, mental, and community health effects on the southern Louisiana women exposed to the oil spill and discovered that they were associated with an increase in self-reported physical health outcomes.…”
Section: Response and Clean-up Operations In Event Of Oil Spillagementioning
confidence: 99%
“…depression and anxiety disorder) (Adams et al, 2011;Bromet et al, 2011). The 2010 Deepwater Horizon oil spill had a deleterious effect on psychological well-being and also on the social and cultural life of local coastal residents (Lee et al, 2016). Technological disasters can lead people to hold more negative attitude toward the relevant technologies (Eiser et al, 1989;Verplanken, 1989;Huang et al, 2013;Visschers and Siegrist, 2013), which is the focus of our study.…”
Section: Introductionmentioning
confidence: 97%
“…Despite evidence that oil spills bring a unique set of stressors and are associated with mental health effects (Chang et al, 2014;Osofsky et al, 2010), predictors of worry among coastal communities along the Gulf of Mexico about ongoing impacts have received little attention from researchers (for an exception, see Lee, Rehner, Choi, Bougere, & Osowski, 2016). In the years after the well causing the DH oil spill was capped, little research has examined the extent to which worry about the health, economic, and social sequelae of the DH oil spill is associated with different types or amounts of indirect exposure, prior traumatic experiences, and other sociodemographic characteristics.…”
Section: Introductionmentioning
confidence: 99%